Penggunaan Metode Role Play pada Materi Tugas Pemimpin Daerah Kelas III SD Negeri 002 Palembang - Anggun Sari; Dewi Anggraeni; Murjainah Murjainah; Putri Gerry Sandari (Jurnal Ilmu Bahasa dan Pendidikan Guru Sekolah Dasar, 2026)
This study was conducted based on the low level of student activeness and understanding in IPAS learning at the elementary school level. The objective of this research was to determine the effectiveness of the role play method in improving students’ activeness and learning outcomes. This study employed a classroom action research approach involving 27 students. The data were collected through observation and evaluation of student learning outcomes. The findings revealed a significant improvement in both student participation and understanding after the implementation of the role play method. Students became more active in asking questions, responding to the teacher, and participating in classroom activities. In terms of learning outcomes, 85.2% of students were able to answer questions correctly and demonstrated good understanding, while the remaining 14.8% also achieved the minimum criteria. These results indicate that learning through direct experience enhances students’ comprehension. The implication of this study suggests that the role play method can be used as an effective alternative teaching strategy to create an interactive, engaging, and student-centered learning environment in elementary education.